Fatigue crack growth behavior of additively manufactured 17-4 PH stainless steel: Effects of build orientation and microstructure. (June 2019) - Nezhadfar, P.D.; Burford, Emma; Anderson-Wedge, Kathryn; Zhang, Bin; Shao, Shuai; Daniewicz, S.R.; Shamsaei, Nima
Graphical abstract: Highlights: Fatigue crack growth behavior of laser powder bed fused 17-4 PH SS was investigated. Effect of heat treatment and microstructure on crack growth behavior was studied. Depending on heat treatment, build orientation effect on crack growth was observed. Fractography analysis was performed to understand the crack growth mechanism. δ-ferrite and martensite weak interfaces caused cracking in H1025 specimens. Abstract: Additive manufacturing (AM) brings more freedom to design and fabricate parts with complex geometries. However, structural integrity of additively manufactured parts must be thoroughly investigated before they can be used in critical, load bearing structural applications. This study investigates the fatigue crack growth (FCG) behavior of 17-4 precipitation hardening (PH) stainless steel (SS) fabricated using laser powder bed fusion (L-PBF) process, and compares it to that of wrought counterpart. The effect of different heat treatment procedures and the notch orientation relative to the build direction were also studied. FCG tests were conducted under force-controlled mode at room temperature with a load ratio of R = 0.1 and a frequency of 10 Hz up to fracture. Microstructure characterization and fractography analysis were carried out to elaborate the crack growth mechanism with respect to different heat treatment conditions and crack growth directions. Abnormal FCG behavior was observed for L-PBF 17-4 PH SS subjected to H1025 heat treatment procedure. This was associated with the presence of δ-ferrite and its weak interface with martensite boundaries. However, L-PBF 17-4 PH SS specimens subjected to CA-H900 condition were found to behave similar to the wrought counterparts in the Paris regime.